The grammatical category of case as an hierarchical system - A L Novikov; M A Rybakov (Russian journal of linguistics: Vestnik RUDN, 2013)
The problem of an hierarchical structure of the category of case is being raised in the article, which also deals with the criteria and goals of its study. The review of different attitudes to semantic organization of the category of case is also given in the paper, the principles of structuring the category are considered.